Arbuscular Mycorrhizal Fungi and Bacterial Populations on Mycorrhizosphere of trembesi (Samanea saman (Jacq.) Merrill): Keragaman Fungi Mikoriza di Rhizosfer Trembesi - Budi, Sri Wilarso; Octaverina, Shinta Kartika (Journal of Tropical Silviculture, 2024)
Mycorrhizosphere is the area around the roots of plants that have mycorrhizae and generally contain many microorganisms. The aim of this research was to analyze the number of Aarbuscular Mycorrhizae Fungi (AMF) spores, populations, and morphological characteristics of bacteria in the mycorrhizosphere of trembesi seedlings growing in post-mining media in organic pot containers. The experimental design used was a Completely Randomized Design (CRD) with split plot design consisting of 3 factors, namely AMF, organic pot composition, and size of potting material. The results showed that the interaction of AMF inoculation factors and pot composition had a significant effect on the number of AMF spores, the percentage of root colonization, and the number of bacterial colonies. The combination of treatment with AMF inoculation using a pot composition of 45% newspaper, 35% compost (bokashi), 0% Cocopeat, 0% Rock phosphate was able to increase the number of AMF spores in organic pots and media as well as the percentage of root colonization. The dominant character of the bacterial colony is milky white, round in shape, smooth/flat edges, and convex elevation. Keywords: Aarbuscular Mycorrhizae Fungi, bacteria, correlation, rhizosphere, trembesi